Effect of Moringa Flower Extract (Moringa Oleifera) on Collagenization and Histopathology of Skin Tissue in the Healing of Dermapen Scars in Obese Male Wistar White Rats - Soraya Tanjung, Dian; Kurniawati, Rachmi; Adi Mylano, Tri (CV. Inara, 2024)
Injury can be accidental, intentional, or disease-related. Moringa leaves may help heal wounds. The research aims to test and assess the effects of Moringa oleifera flower extract on dermapen wound healing collagenization in male Wistar strain white rats, an obese model, and their histological findings—quantitative True Experimental Study with Post-Test Only Control Group Design. Twenty-four male Wistar white rats (Rattus norvegicus) were sampled. Accumulation of Test Animals, Moringa Flower Extract Preparation, Phytochemical Screening / Secondary Metabolite Test, Treatment Process (200, 400, and mg/kgBW of Moringa flower extract), Wound Observation, Histopathological Skin Preparations, and Histopathological Examination of Preparations were the research procedures. Window data was analyzed using SPSS 25.0 and One Way ANOVA with a 95% confidence level (p < 0.05). The Post Hoc Test with LSD was used for further analysis. The research results found Moringa flower extract at 200mg/Kg BW, 400mg/KgBW, and 600mg/KgBW could expedite wound healing and improve collagen density in obese mice's dermapen wounds. The 600mg dose was most beneficial. Research conclusions: Moringa flower extract aids dermapen wound healing, collagenization, and obesity weight loss, according to a study.